Style d'intervention pédagogique, relations affectives enseignants-étudiants et engagement par rapport à la matière - Bujold, Neree; Saint-Pierre, Henri (Canadian Journal of Higher Education, 1996)
Many faculties deplore the fact that too many students seem to study only to obtain school marks and afterwards rapidly forget what they have learned. Consequently, they meet with difficulties when transfering knowledge in other courses. A correlative research explored this problem by testing three hypotheses concerning the relation between the faculty's teaching style, the quality of their relationship with their students and the latter's involvement in subject learning. Interaction was also tested between these three variables and other confounding variables (nuisance variables). Ninety-four teachers, including faculties and part- time lecturers chosen at random on the Université Laval campus, answered a survey measuring their perception of their teaching style. Over three thousand of their students also answered a survey measuring their perception of their teacher's teaching style, the closeness relationship with their teacher, satisfaction with their teacher's style, positiveness of their feelings for their teacher, global satisfaction with the course and involvement in learning the subject taught by the teacher. Significant correlations were found between the main variables. Significant interactions were also found with certain confounding (nuisance) variables.